Effect of powdery mildew infection on the antioxidant enzyme activities in different lines of Thatcher-based wheat - Kovács, Viktória (Acta Biologica Szegediensis, 2011)
Changes of antioxidant enzyme activities (glutathione reductase, glutathione-S-transferase, catalase, ascorbate peroxidase and guaiacol peroxidase) were studied in four near-isogenic Thatcher-based wheat lines following powdery mildew infection. The activities of ascorbate peroxidase and guaiacol peroxidase were increased significantly after 7 days of infection in all lines. Significant increases were observed in glutathione-S-transferase activity in the lines carrying Lr33, Lr26 and Lr19 genes, furthermore in catalase and glutathione reductase activity in the case of lines with Lr26 and Lr19 genes on the 7th day of infection. Changes in enzyme activities, caused by aging, were also detected in all lines. Four peroxidase isozymes,minduced by infection, were found by gelelectrophoresis.